INCREASING EDUCATION GAP DUE TO DISPARITY IN ACCESS TO TECHNOLOGY - Loso Judijanto; Melyana R Pugu; Achmad Farchan (International Journal of Teaching and Learning, 2025)
Disparities in access to technology and the gap to education are critical issues that span communities around the world, especially among low-income groups and in remote areas. The research method used was a literature review. The results show that limited access to technology in education results in low academic achievement and students' lack of readiness to face work demands in the digital era. Furthermore, students from low-income families and remote areas are most affected, with a greater likelihood of falling behind in digital literacy and independent learning skills.